Le condizioni di crescita della democrazia dei luoghi - Magnaghi, Alberto (Scienze del Territorio, 2020)
Assuming that a democracy of places can only be a community democracy, the paper seeks for the conditions that can foster its growth; and finds them in the analytical and proactive application of the concept of urban bioregion, apt to activate territorial visions and practices that bring together, on the one hand, the recognition, re-appropriation and enhancement of local territorial heritages by “concrete communities” of dwellers-producers, on the other hand entrusting their management, as common goods, to new institutions of community self-government; connected in a complex architecture of “inter-organizational networks” – horizontal and vertical, subsidiary and non-hierarchical – able to reorient the decision-making vector ‘from below’ and giving rise to a “higher-order local”.